Population, city and environment in contemporary Mexico - Morelos, José B (El Colegio de México, 2006)
This work presents the results of a group of research projects on various aspects of the demographic, urban and environmental problems of present-day Mexico. These projects are a sample of what is currently being researched in Mexico, particularly at the Center for Demographic, Urban and Environmental Studies, El Colegio de México. The articles analyze both the basic, technical and theoretical aspects of the three disciplines referred to above, as well as important issues in decision-making and public policy. Some of the key issues in the evolution of population, urban and environmental problems in recent years that have defined the profile of contemporary Mexico are summarized in the various studies included in this work.